Chemical profiles and pharmacological activities of Chang-Kang-Fang, a multi-herb Chinese medicinal formula, for treating irritable bowel syndrome. (6th April 2017) - Mao, Qian; Shi, Lei; Wang, Zhi-Gang; Luo, Yu-Hui; Wang, Yin-Yu; Li, Xue; Lu, Min; Ju, Jian-Min; Xu, Jin-Di; Kong, Ming; Zhou, Shan-Shan; Shen, Min-Qin; et al.
Abstract: Ethnopharmacological relevance: Chang-Kang-Fang formula (CKF), a multi-herb traditional Chinese medicinal formula, has been clinically used for treatment of irritable bowel syndrome (IBS). The mechanisms of CKF for treating IBS and the components that are responsible for the activities were still unknown. Aim of the study: To investigate the chemical profiles and effects of CKF on IBS model. Materials and methods: The chemical profiles of CKF were investigated by ultra performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (UHPLC-Q/TOF-MS/MS). On colon irritation induced rat neonates IBS model, the influence of CKF on neuropeptides, including substance P (SP), calcitonin gene-related peptide (CGRP), vasoactive intestinal polypeptide (VIP) and 5-hydroxytryptamine (5-HT), were measured by ELISA, and the effect on intestinal sensitivity was assessed based on the abdominal withdrawal reflex (AWR) scores. In addition, the activities of CKF against acetic acid-induced nociceptive responses and prostigmin methylsulfate triggered intestinal propulsion in mice were also evaluated. Results: 80 components were identified or tentatively assigned from CKF, including 11 alkaloids, 20 flavanoids, 4 monoterpenoids, 9 iridoid glycoside, 9 phenylethanoid glycosides, 10 chromones, 7 organic acid, 3 coumarins, 2 triterpene and 5 other compounds. On IBS rat model, CKF was observed to reduce AWR scores and levels of SP, CGRP, VIP and 5-HT. Moreover, CKF reduced the acetic acid-induced writhing scores at all dosages and reduced the intestinal propulsion ration at dosage of 7.5 and 15.0 g/kg/d. Conclusions: CKF could alleviate the symptoms of IBS by modulating the brain–gut axis through increasing the production of neuropeptides such as CGRP, VIP, 5-HT and SP, releasing pain and reversing disorders of intestinal propulsion. Berberine, paeoniflorin, acteoside, flavonoids and chromones may be responsible for the multi-bioactivities of CKF. Graphical abstract: